A compact in-blade five hole pressure probe for local inflow study on a horizontal axis wind turbine. Issue 4 (August 2016) - Moscardi, Andrea; Johnson, David A
Understanding local inflow conditions on a wind turbine blade on an operating wind turbine can further understanding of aerodynamic variations and help predict loads on the turbine. Turbine blades are generally designed with a two-dimensional steady approach, however the real wind conditions are highly three-dimensional (3D) and unsteady. Detailed measurements are not common for validating aerodynamic models. The aim of this theoretical and experimental study is to build, calibrate, install and test a compact in-blade five hole pressure probe system to be used to retrieve these measurements. Wind tunnel calibration of the five hole pressure probe has been successfully completed using an automated traversing system over a ±45° range, with 5° increments. Error analysis showed that the multi-zone pressure coefficient data reduction approach is the most suitable for this application. This approach not only extends the measurable local inflow angles up to ±70°, but also it allows any reference pressure for differential pressure readings. A new data acquisition system (DAQ) internal to a rotating small wind turbine blade section was developed. Space limitations resulted in a custom built DAQ of very contained dimensions. This included, among others, five pressure transducers on a printed circuit board, a 16 bit analog to digital converter, an Arduino microcontroller, and a Bluetooth transceiver to transmit the data wirelessly to the main computer. The new blade section was designed and 3D-printed in such a way that the DAQ instrumentation could be easily accessed and, at the same time, had an acceptable structural solidity. A series of tests were conducted on a 3.4 m diameter wind turbine in a large scale wind tunnel in order to assess the correct functioning of the probe system. As expected, the inflow measurement obtained while the turbine was operating under yawed conditions showed a periodically oscillating inflow vector. The period of this variation was the same as the period of the rotor rotation.